Risks Elaborated vs. Risks Downplayed: The Effect of Risk Comparisons in Mainstream Media During Covid-19 on Risk Perceptions and Anxiety Levels - Anderson, Ashley A.; Sivakumar, Gayathri (Frontiers in Communication, 2021)
This study examines the effects of risk comparisons in mainstream media during the Covid-19 outbreak that either expressed the severity of the outbreak or downplayed it by comparing the mortality rates of the disease to other risks. In an online experiment of undergraduate students at a large university in the U.S. Mountain West (n = 78) in early May 2020, we found trust in government agencies played an important role in how people interpret risk messages in media. When the risks are amplified, those who held low levels of trust in government agencies are more likely to report higher levels of anxiety. When risks are downplayed, people who hold high levels of trust in government agencies are more likely to report greater risk perceptions than those who hold low trust in government agencies. Implications are discussed.